Organic contaminants of emerging concern in leachate of historic municipal landfills. (1st May 2021) - Propp, Victoria R.; De Silva, Amila O.; Spencer, Christine; Brown, Susan J.; Catingan, Sara D.; Smith, James E.; Roy, James W.
Abstract: Many types of contaminants of emerging concern (CECs), including per- and poly-fluoroalkyl substances (PFAS), have been found in leachate of operating municipal landfills. However, there is only limited information on CECs presence in leachate of historic landfills (≥3 decades since closure, often lacking engineered liners or leachate collection systems) at concentrations that may pose a risk to nearby wells and surface water ecosystems. In this study, 48 samples of leachate-impacted groundwater were collected from 20 historic landfills in Ontario, Canada. The CECs measured included artificial sweeteners (ASs), PFAS, organophosphate esters (OPE), pharmaceuticals, bisphenols, sulfamic acid, perchlorate, and substituted phenols. The common presence of the AS saccharin, a known indicator of old landfill leachate, combined with mostly negligible levels of the AS acesulfame, an indicator of modern wastewater, revealed that most samples were strongly influenced by leachate and not cross-contaminated by wastewater (which can contain these same CECs). Several landfills, including ones closed in the 1960s, had total PFAS concentrations similar to those previously measured at modern landfills, with a maximum observed here of 12.7 μg/L. Notably elevated concentrations of several OPE, sulfamic acid, cotinine, and bisphenols A and S were found at many 30-60 year-old landfills. There was little indication of declining concentrations with landfill age, suggesting historic landfills can be long-term sources of CECs to groundwater and that certain CECs may be useful tracers for historic landfill leachate. These findings provide guidance on which CECs may require monitoring at historic landfill sites and wastewater treatment plants receiving their effluent. Graphical abstract: Image 1 Highlights: There is little information on contaminants of emerging concern (CECs) in historic landfills. Per- and poly-fluoroalkyl substances (PFAS) were prevalent in historic landfills. PFAS and other CECs concentrations often similar to those found in modern landfills. PFAS and other CECs showed persistence in landfills closed 60 or more years.